EFISIENSI SISTEM KOMUNIKASI MODERN DALAM KEGIATAN TRANSAKSI PADA BISNIS WARKOP BERKAH - Dian G Purba; Faisal A Siadari; Tommi H Damanik; Jhoni F Manurung; Fadilah R M Siregar (LPPM Politeknik Pratama, 2024)
This research aims to analyze the efficiency of modern communication systems in transaction activities at Warkop Berkah, a micro-enterprise that has adopted digital technology. The main focus of the research is the implementation of modern communication systems, such as cashless payments via digital wallets, QR codes, and Point-of-Sale (POS) applications, which aim to improve operational efficiency, customer experience, and business competitiveness. This research also identifies various challenges faced in implementing this technology, including the need for employee training, implementation costs, and adaptation by customers who are still accustomed to conventional systems. The research results show that modern communication systems have a significant impact in increasing operational efficiency at Warkop Berkah. Transaction processes become faster, the risk of calculation errors is reduced, and financial transparency increases. In addition, this technology provides a better customer experience by offering convenience, security and comfort, especially for the younger generation who are more familiar with technology. However, technology adoption also faces obstacles, such as dependence on stable internet connections, resistance from certain customers, and technical challenges in system maintenance. To overcome this challenge, the research recommends several strategies, including intensive training for employees, customer education, diversification of payment methods, and improving technological infrastructure. Real-time monitoring of transaction data is also proposed as a step to optimize operational performance and maximize customer experience. By implementing the right strategy, Warkop Berkah can utilize modern communication systems to support the sustainability and competitiveness of its business. This research contributes to understanding the importance of digitalization in micro and small businesses (MSMEs) in facing the challenges of the digital era. In addition, this study provides practical insights for micro business owners who want to adopt modern technology to increase efficiency and business growth amidst increasingly fierce competition.